1985
DOI: 10.1007/bf01412958
|View full text |Cite
|
Sign up to set email alerts
|

Determination of charge density of anionic polyacrylamide flocculants by NMR and DSC

Abstract: New methods are suggested for the determination of the charge density of acrylamide/acrylate copolymers. 13C nuclear magnetic resonance spectroscopy was used to determine the comonomer ratio by comparing the peak intensities of the methine carbon in acrylamide and acrylate monomers. Results were compared with those obtained by conductometric and potentiometric titration and were found to be in good agreement. Differential scanning calorimetry was employed to determine the glass transition temperatures (T~) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
2
4
0
Order By: Relevance
“…TGA was performed on PAM and silica–PAM microparticle samples, as reported in Figure g. The two materials had similar mass loss profiles, with two major loss events occurring at 250 and 400 °C, in agreement with literature results for PAM-containing materials. , The primary difference between the two materials sampled was the final mass retained, with the silica-containing sample retaining 33.8% of its initial mass, whereas the bare polymer sample retained only 20.1% (in agreement with previous literature). This indicated that silica accounts for 13.7% of the total (dry) mass of the polymer, providing further evidence of the successful deposition of silica.…”
Section: Resultssupporting
confidence: 88%
“…TGA was performed on PAM and silica–PAM microparticle samples, as reported in Figure g. The two materials had similar mass loss profiles, with two major loss events occurring at 250 and 400 °C, in agreement with literature results for PAM-containing materials. , The primary difference between the two materials sampled was the final mass retained, with the silica-containing sample retaining 33.8% of its initial mass, whereas the bare polymer sample retained only 20.1% (in agreement with previous literature). This indicated that silica accounts for 13.7% of the total (dry) mass of the polymer, providing further evidence of the successful deposition of silica.…”
Section: Resultssupporting
confidence: 88%
“…When the gel is placed in a 2 M NaOH solution, the amine groups are converted into ionized carboxylic groups. The maximum efficiency of the groups conversion is about 20% 1, 25. Charges on the gel network are set by the –COO − groups and are neutralized by Na + counter ions.…”
Section: Resultsmentioning
confidence: 99%
“…When the gel is placed in 2 M NaOH solution, conversion of amine groups into ionized carboxylic groups occurs. In a highly ionized polyacrylamide gel, the fraction of the carboxyl groups ionized at any moment is about 20 percent 2,27 Charges on the polymer chains are set by the -COO À groups and are neutralized inside the gel by Na + counterions. The gel is then placed in an excess of demineralised and deionised water, and since the concentration of the free ions inside the gel is not equal to that in the outer solution, a counterion osmotic pressure difference is created.…”
Section: Methodsmentioning
confidence: 99%